Anthropogenic and climatic drivers of alpine wetland degradation: a multi-scale perspective - Zhang, Wenling; Cheng, Qitai; Li, Fei; Kumar, Amit; Qin, Guiyong; Liu, Lu; Hui, Dafeng; Li, Hepeng; Yuan, Xia; Liu, Dan (Frontiers in Forests and Global Change, 2025)
Alpine wetlands play a vital role in water storage, ecosystem services, biodiversity conservation, material recycling, climate change mitigation, and environmental purification. At present, these high-elevation and high-latitude ecosystems are facing dual threats from the combined impacts of climate change and human activities. This perspective reveals that climate-related factors such as phenological changes and plant migrations, as well as human activities like agricultural reclamation, have significantly damaged these ecosystems. To address alpine wetland degradation, multiple strategies are proposed through integrated approaches. First, exploring the synergistic application of multiple restoration techniques, including ditch-filling, terrain-leveling, invasive species removal, and vegetation restoration. Second, establishing long-term ecological monitoring frameworks, including extreme climate and water level monitoring, vegetation and soil survey, among others. Third, sustained investments in scientific research and active public awareness and stakeholder engagement. Through these comprehensive efforts, integrating traditional ecological knowledge with modern restoration techniques, we can jointly safeguard biodiversity, maintain ecosystem services, mitigate the degradation of alpine wetlands and preserve these high-value ecological systems for future generations.